The Effect of Emotional Intelligence on the Mathematical Problem-Solving Ability of Fifth Grade Students Elementary School in Tanara - Ulfah, Maria; Sopandi, Wahyu; Supriadi; Novia, Gita (International Conference on Elementary Education, 2025)
Mathematics learning in elementary school requires a balance between cognitive abilities and emotional management. Students with good emotional intelligence tend to be able to control anxiety, focus on solving steps, and be persistent in facing complex problems. Observations at Gusguntur Elementary School in Tanara District show that some fifth-grade students still have difficulty managing their emotions when solving problems. This study aims to determine the effect of emotional intelligence on students' mathematical problem-solving abilities. The study uses a quantitative approach with an ex post facto design. The sample consists of 40 fifth-grade students selected by saturated sampling. The instruments used are emotional intelligence questionnaires and mathematical problem-solving tests. The data were analyzed using simple linear regression. The results showed a significant influence between emotional intelligence and mathematical problem-solving abilities with a significance value of 0.012 < 0.05 and a coefficient of determination (R²) of 0.31. The higher the students' emotional intelligence, the better their ability to understand problems, choose strategies, and solve mathematical problems effectively.